Efficacy of Alpha Keto-Analogues in The Management of Chronic Kidney Disease - Umar, Saba; Sabir, Sohail; Altaf, Ashfaq; Raja, Khalid Mahmood; Siddiqi, Fuad Ahmed; Saleem, Salman; Azam, Malik Nadeem; Sabir, Haroon (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the efficacy of alpha keto-analogues in the management of chronic kidney disease at a tertiary care hospital. Study Design: Quasi-experimental study. Place and Duration of Study: Nephrology Department, Armed Forces Institute of Urology, Rawalpindi from Jul to Dec 2020. Methodology: A total of 300 patients of chronic kidney disease stage 3 and 4, not dependent on hemodialysis were included in the study. They were divided into two groups with matched age, gender and duration of chronic kidney disease. Group-I received the routine treatment of chronic kidney disease with low protein diet while group-II received alpha keto-analogue in standard dose in addition to routine treatment of chronic kidney disease with low protein diet. Estimated glomerular filtration rate was assessed at the baseline and after six months. Results: Out of 300 patients 151 (50.3%) were males while 149 (49.7%) were female patients. 110 (36.7%) patients had stage-3 disease while 190 (63.3%) had stage-4 chronic kidney disease. Mean difference of eGFR in group-I was 3.17 ± 3.19 mL/min/ 1.73m2 while mean difference of eGFR in group-II was 1.16 ± 1.52 mL/min/1.73m2 (p-value<0.001). Conclusion: Alpha keto-analogues emerged as an efficacious short-term option in reducing the progression of chronic kidney disease in our study. Use of this option in addition to routine treatment and low protein diet was related to significant improvement in renal functions.